Pursuing the humanity of subalterns on the farm in Zimbabwean literature. - Nyoni, Erick; Naidoo, Salachi (University of South Africa Press, 2020)
The subalterns on the Zimbabwean farm are an intriguing but seemingly forgotten groups. Not many literary critics have made them a subject of their studies .The sparseness of work related to the marginalised farm worker is quite conspicuous. Farm workers have remained insignificant and just appear as objects important for their hands and not for the humanity behind their hands ..........................................................